2017
DOI: 10.1097/phm.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Different Deep Dry Needling Dosages in the Treatment of Patients With Cervical Myofascial Pain

Abstract: DDN in the upper trapezius MTrP improved pain at a 1-wk follow-up, but improvements were not significantly different among DDN dosages. A higher number of patients with neck pain improvements superior to the moderate clinically important differences were observed when eliciting 6 LTRs and LTRs until exhaustion compared with not eliciting LTRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 26 publications
1
38
0
2
Order By: Relevance
“…Previous research has showed similar results with regard to the proportion of patients with neck pain who perceived postneedling soreness in the upper trapezius [13,[40][41][42]. In the present study, 94.2% of patients presented postneedling soreness, whereas other studies observed proportions of 55% [40,41], 88% [42], or 91.4% [13].…”
Section: Postneedling Sorenesssupporting
confidence: 82%
See 3 more Smart Citations
“…Previous research has showed similar results with regard to the proportion of patients with neck pain who perceived postneedling soreness in the upper trapezius [13,[40][41][42]. In the present study, 94.2% of patients presented postneedling soreness, whereas other studies observed proportions of 55% [40,41], 88% [42], or 91.4% [13].…”
Section: Postneedling Sorenesssupporting
confidence: 82%
“…Multiple insertions are necessary to elicit LTRs until exhaustion, whereas low‐dosage techniques only require few insertions. A recent study investigated the clinical effectiveness of different dosages of DDN and did not show significant differences between groups, but high dosages seem to be associated with greater clinical relevance of pain improvements [13]. However, high DDN dosages may be associated with increased levels of postneedling soreness.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…81 Many randomized trials have evaluated trigger point injections, but they generally have methodological flaws such as use as a standalone treatment and the lack of a true placebo group (dry needling could be beneficial). 82 Some evidence suggests that trigger point injections alone are not more effective than less invasive treatments such as laser and ultrasound, and that injections with anything, including saline, are better tolerated and more effective than dry needling. [83][84][85] One randomized trial in 80 people with chronic whiplash disorders found no significant benefit for dry needling with exercise compared with exercise and sham needling.…”
Section: Myofascial Painmentioning
confidence: 99%